Peningkatan Kemampuan Penanganan Kegawatdaruratan Medis di Alam Terbuka pada Siswa Pecinta Alam - Pratama Yulianto; Rian Maulana Yusup; Hygma Fauzy; Windri Dewi Ayu; Ahmad Jaelani; Tresna Komalasari (Yayasan Inspirasi El Burhani, 2026)
Introduction: Outdoor activities among students are becoming increasingly popular as a means of character building, improving physical and mental health, and fostering environmental awareness. The lack of first aid knowledge and skills among student nature enthusiasts increases the potential for complications, including death, in remote locations with limited medical access. Objective: The objective of this community service initiative is to enhance the skills of outdoor enthusiasts in Majalengka Regency regarding the management of medical emergencies in the outdoors through theoretical instruction, demonstrations, and practical simulations. Method: The program took place on February 1, 2026, in an open-air setting in Majalengka Village, involving 25 groups or 150 students. Theoretical instruction and demonstrations were provided for 60 minutes, followed by a hands-on trauma management simulation. The assessment instrument used a first aid observation sheet. Data were analyzed descriptively using frequency distributions and percentages. Result: The results of the observations showed that out of 25 groups, 10 groups (40.0%) received a “good” rating, 12 groups (48.0%) received a “fair” rating, and 3 groups (12.0%) received a “poor” rating. Overall, 88.0% of the groups achieved an adequate level of skill in handling medical emergencies in the outdoors. This program enhances students’ competence and confidence in providing first aid in remote environments. Conclusion: This community service program successfully improved the skills of nature-loving students in handling medical emergencies in the outdoors. The collaborative approach and practical simulations proved effective.